A novel approach to assess occupational risks and prevention of hazards: the house of safety & prevention - Cinar, Ulas; Cebi, Selcuk (IOS PRESS, 2022)
Risk management is the key factor to obtain safety in the working environment and its effectiveness increases with accuracy assessment and robust analysis. However, it is hard to succeed because of uncertainties in the working environment. Therefore, there are a lot of risk assessment methods in the literature to assess occupational health and safety risks. The traditional risk assessment methods handle each activity in the working environment separately and they do not consider the interactions among them. Furthermore, in these methods, potential outcomes of the risk parameters are considered based on the most possible outcome although there may be more than one potential outcome. Differ from the traditional methods, The House of Safety method has been proposed to consider all potential outcomes and handle the interactions among the activities. In this study, an extension of The House of Safety is proposed to consider interactions among potential risks and to determine the most effective prevention method based on the potential risks. Hence, this extension provides an evaluation of the whole system. The proposed model has been developed by integrating Fuzzy Inference System (FIS), Fuzzy Analytical Hierarchy Process (FAHP), and DEMATEL into Quality Function Deployment (QFD). In this direction, FIS is used to determine activity-related probabilities, FAHP is utilized to identify all possible damage potentials of risks, and the DEMATEL is used to clarify interactions among risks. Finally, all information produced by these methods were aggregated to obtain total risk scores by using QFD. In addition, a second home has been created to link prevention and risks. Therefore, an effective prevention plan has been made to eliminate priority risks with all effective parameters. This stage provides the opportunity for optimum prevention plan against risk or risk groups dominating the system at the same time. In this study, unlike traditional methods including a partial risk assessment perspective, an integrated method that takes into account the risks on their own and the interactions between them is proposed in the literature, and the proposed approach has been applied to an open pit mine.
Keywords: The house of safety; risk assessment method; occupational safety; fuzzy inference system; fuzzy AHP; DEMATEL; QFD; ENVIRONMENT; HEALTH; MODEL; Computer Science